Assessing women's understandings of health in rural Papua New Guinea: Implications for health policy and practice - Hinton, Rachael; Earnest, Jaya (Blackwell Publishers, 2011)
In Papua New Guinea (PNG), women’s health is addressed by applying biomedical solutions which often ignore the complexity of women’s histories, cultural contexts and lived experiences. The objective of this study was to examine adult and older women’s perceptions of health and well-being to identify priority areas for public service interventions. Rapid ethnographic assessment was conducted in the Wosera district, a rural area of PNG from mid-2005 to early 2006, to examine the health concerns of women. Twenty-seven adult women and 10 older women participated in the study. Health was not limited to one aspect of a woman’s life, such as their biology or maternal roles; it was also connected with the social, cultural and spiritual dimensions of women’s daily existence. Participants also identified access to money and supportive interpersonal relationships as significant for good health. A disconnect was found to exist between women’s understandings of good health and socio-political health policies in PNG, something likely to be repeated in health service delivery to different cultural groups across the Asia Pacific region. Health and development practitioners in PNG must become responsive to the complexity of women’s social relationships and to issues relating to the context of women’s empowerment in their programmes.